2022
DOI: 10.32479/ijeep.13648
|View full text |Cite
|
Sign up to set email alerts
|

Does Green Supply Chain Management Improve Sustainable Performance?

Abstract: The process of Green Supply Chain Management (GSCM) is widely associated with its contribution to the company's sustainability performance. The GSCM process will also be linked to an integrated system of Enterprise Resource Planning (ERP) that affects the achievement of sustainability performance. The importance of environmental consciousness from producers to direct their business processes that are beneficial to the environment in the long term. This study used 507 samples of manufacturing companies in Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Al-Bazali and Al-Zuhair (2022) utilized fuzzy logic to comprehensively assess the sustainability of the oil and gas industry. Moreover, Rizki et al (2022) combined green supply chain management (GSCM), enterprise resource planning (ERP), and environmental consciousness to enhance sustainability performance in manufacturing companies. In a more industry-specific context, Dally et al (2020) examined the interplay between personal carbon trading and carbon knowledge management to assess their combined impact on environmental sustainability in Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al-Bazali and Al-Zuhair (2022) utilized fuzzy logic to comprehensively assess the sustainability of the oil and gas industry. Moreover, Rizki et al (2022) combined green supply chain management (GSCM), enterprise resource planning (ERP), and environmental consciousness to enhance sustainability performance in manufacturing companies. In a more industry-specific context, Dally et al (2020) examined the interplay between personal carbon trading and carbon knowledge management to assess their combined impact on environmental sustainability in Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same way, Umar et al (2021a) reported in the literature that there is a strong association between sustainable practices and different circular-economy practices within the organization. Furthermore, in a study by Rizki et al (2022) based on the geography of Thailand it is shown that there is a significant relationship between green purchasing practices and the eco-performance of the firm. In contrast, Zhang et al (2017) found a negative association between GSCM and the firm's productivity.…”
Section: Industry 40 and Green Supply Chain Managementmentioning
confidence: 99%